ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK YANG BERKEMBANG MELALUI PUTUSAN HAKIM - Tri Cahya Indra Permana (Universitas Muhammadiyah Tangerang, 2020)
General principles of good governance developed by judge decision. Those general principles must be obeyed by government officials. Some of new principles made by judges among other things : principles of ultra petita, principles of prohibition of issued a decree who has been cancelled by the court, and principles of government foult can not disadvantage people. The aim of the developing general principles of good governance is to solve the administrative law problems.